Fading Echoes of Tradition: The Transformation of Intergenerational Farming Knowledge in Toto Tribal Communities - Suman, Swati; Deb, Atanu; Kumar Prusty, Ajay; Bhadra, Preetha (Indian Journal of Extension Education, 2025)
Indigenous knowledge systems have traditionally played an important role in supporting agricultural livelihoods, particularly in tribal populations. The Toto tribe, an endangered indigenous population in West Bengal, India, has relied on intergenerational knowledge transmission to ensure sustainable farming practices but their traditional wisdom is at risk due to socio-economic changes and modernization. The study examines the various socio economic factors influencing the transmission of agricultural knowledge within Toto family farms, analyzing the impact of intergenerational exchange on agricultural sustainability. A mixed-methods approach was employed, integrating qualitative participatory research with quantitative data analysis. Data were collected through Focus Group Discussions, personal interviews, participant observation and structured household surveys among 120 Toto family farms in Totopara village. Pearson’s Correlation Analysis assessed socio-economic factors influencing livelihood choices, while thematic coding in ATLAS.ti identified patterns of knowledge retention and transformation. The study reveals a generational gap in farming knowledge due to shifts in aspirations, formal education, and reduced reliance on traditional farming techniques. Modernization has improved efficiency but displaced indigenous methods like seed preservation and water conservation. Integrating traditional knowledge with modern advancements is crucial for climate-resilient and sustainable farming. Policy interventions, community-led conservation efforts and indigenous education programs are critical for preserving agricultural heritage.
Keywords: Intergenerational knowledge; Livelihood; Modernization; Thematic analysis; Toto tribe